ANALYZING SENTENCE PATTERN LEARNING AND ITS RELATIONSHIP TO VOCATIONAL HIGH SCHOOL STUDENTS' READING COMPREHENSION - Bahagia Saragih; Putri Grace Simanjuntak; Dhany Samuel Sirait; Maximus Naiborhu; Krisjhon Martua Siallagan; Shaquille Adam Rafa Dhero (STKIP Subang, 2026)
This study aims to investigate the relationship between students' sentence pattern knowledge and reading comprehension ability at SMK Negeri 7 Medan. A quantitative approach was used, with 30 10th-grade students in the 2025/2026 academic year. Data were collected using two tests: a sentence pattern test with 14 items and a reading comprehension test with 6 multiple-choice questions. The obtained scores were compared using descriptive statistics and the Pearson Product-Moment correlation formula. The results showed that students' average score in sentence pattern mastery was 8.0 and their average score in reading comprehension was 3.6. The correlation coefficient (r) was 0.558, indicating a moderate positive relationship between the two variables. This indicates that students with a better understanding of sentence patterns performed better in reading comprehension. These findings suggest that sentence pattern mastery contributes significantly to students' reading comprehension. Therefore, English teachers are encouraged to integrate grammar lessons, especially about sentence structure, into reading classes to improve students' comprehension abilities.